Perkembangan Islam masa Umayyah: Tinjauan sejarah peradaban Islam - Damayanti, Liya (Maliki Interdisciplinary Journal, 2026)
The Umayyad Dynasty (661–750 CE) was the first dynasty in Islamic history, centered in Damascus. This period was marked by a shift in leadership from a deliberative caliphate to a hereditary monarchy. The Umayyad Dynasty contributed to the expansion of Islamic territory, the development of government administration, and the growth of the intellectual dynamism of the Muslim community. However, various political problems, social disparities, and internal conflicts contributed to the decline of this dynasty. This article examines the development of Islam during the Umayyad Dynasty, highlighting the process of appointing caliphs, the model of government, the profiles of caliphs, political dynamics, intellectual dynamics, and the factors of its decline. This research uses a historical study method with a descriptive-analytical approach to primary and secondary sources, such as classical Islamic historical works and contemporary academic studies. The analysis focuses on the relationship between political policies, government structures, and socio-religious developments during the Umayyad Dynasty. The results of the study show that the initial stability of the Umayyad government played a significant role in expanding Islamic territory and establishing a relatively centralized administrative system, but at the same time gave rise to resistance from various groups due to the practice of power that tended to be exclusive. The intellectual dynamics during this period developed through the codification of early Islamic knowledge and interaction with local cultures in conquered territories. In conclusion, the Umayyad Dynasty played a significant role in establishing the political foundations and Islamic civilization, although internal weaknesses and political conflicts were the main factors that accelerated its collapse.